On parallelizing dual decomposition in stochastic integer programming - Lubin, Miles; Martin, Kipp; Petra, Cosmin G.; Sandıkçı, Burhaneddin (Operations research letters, 2013)
For stochastic mixed-integer programs, we revisit the dual decomposition algorithm of Carøe and Schultz from a computational perspective with the aim of its parallelization. We address an important bottleneck of parallel execution by identifying a formulation that permits the parallel solution of the master program by using structure-exploiting interior-point solvers. Our results demonstrate the potential for parallel speedup and the importance of regularization (stabilization) in the dual optimization. Load imbalance is identified as a remaining barrier to parallel scalability.